Análisis comparativo entre la gerencia oriental y occidental para la toma de decisiones (2018)
The present work proposes a comparison of two styles of managements used throughout the world and it respective thoughts; the western management characterized by its interests in the results and processes and the eastern management characterized by it methodologies for the resolution of organizational problems and the interaction with the employees.